2015
DOI: 10.1002/app.42500
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the thermostability of poly(ethylene terephthalate)–hemp fiber composites: Extending natural fiber reinforcements to high‐melting thermoplastics

Abstract: The thermal stability of poly(ethylene terephthalate) reinforced with 1, 5, 10, 15, and 20% hemp fibers was investigated with the aim of extending the applications of biocomposites to high-melting thermoplastics. The material was injection-molded following compounding with a torque-based Rheomix at 240, 250, and 2608C. A combination of thermogravimetric methods at 5, 10, and 208C/min, Liu and Yu's collecting temperature method, and Friedman's kinetic method were used for testing and analysis. A significant the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…They concluded that addition of additives increased the mechanical properties (elastic modulus and strain at break) of the concerned composite samples. Similarly, Talla et al [32] reported the effect of heating rates on thermostability of the same composite sample. They suggested the possibility of effective melt process of natural fibers/high-melting thermoplastic composites with limited thermal degradation of the reinforcements.…”
Section: Introductionmentioning
confidence: 89%
“…They concluded that addition of additives increased the mechanical properties (elastic modulus and strain at break) of the concerned composite samples. Similarly, Talla et al [32] reported the effect of heating rates on thermostability of the same composite sample. They suggested the possibility of effective melt process of natural fibers/high-melting thermoplastic composites with limited thermal degradation of the reinforcements.…”
Section: Introductionmentioning
confidence: 89%
“…The absorption bands at 1633 cm -1 , 1425 cm -1 , and 1376 cm -1 are characteristic to the stretching C-C, symmetric bending of C-H respectively. The band at 1029 in the composite sample is attributed to the stretching C-O in the lignocellulosic fibers [10][11][12]28], as displayed in Fig. 1.…”
Section: Characterization Of the Composites By Ft-irmentioning
confidence: 91%
“…Among these strategies is the modification of bagasse for metal chelation [2], its use for the production of biofuel and ethanol for industrial purposes [3][4][5] or as raw material in cogeneration plants to produce electric power in Brazil [6,7]. On the other hand, the value of sugarcane bagasse wastes was expanded to its utility as filler in cement [8], or as fiber rich additives in many thermoplastic or thermosetting petroleum polymers based composites including phenol-formaldehyde resins, polyethylene, polypropylene, and poly ethylene-co-vinyl acetate [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…However, as hemp itself contains many impurities and the use of semi-degumming process during spinning, many impurities on the fibers cannot be removed, causing the yarn to form thick details or knots. Due to this, the surface of hemp/organic cotton blended fabric has many hairiness with unclear texture, rough handle and low levelness on it (Min, 2011; Talla et al , 2015; Wei and Chen, 2011; Ranalli and Venturi, 2004; Arthur, 2008; Ali et al , 2012; Zeng and Liu, 2014).…”
Section: Introductionmentioning
confidence: 99%